Evaluation of numerical time-integration schemes for real-time hybrid testing. - Bonnet, P. A.
We present a comparison of methods for the analysis of the numerical substructure in a real-time hybrid test. A multi-tasking strategy is described, which satisfies the various control and numerical requirements. Within this strategy a variety of explicit and implicit time-integration algorithms have been evaluated. Fully implicit schemes can be used in fast hybrid testing via a digital sub-step feedback technique, but it is shown that this approach requires a large amount of computation at each sub-step, making real-time execution difficult for all but the simplest models. In cases where the numerical substructure poses no harsh stability condition, it is shown that the Newmark explicit method offers advantages of speed and accuracy. Where the stability limit of an explicit method cannot be met, one of the several alternatives may be used, such as Chang's modified Newmark scheme or the α-operator splitting method. Appropriate methods of actuator delay compensation are also discussed.
Keywords: Real-time testing; Hybrid simulation; Time-integration schemes